Technika opracowania błękitów w malarstwie gdańskim od połowy XVI do końca XVIII w. - Olszewska-Świetlik, Justyna; Szmelter-Faustek, Bożena (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The technique of blue painting layers was analyzed on the example of selected 27 panel paintings made in Gdańsk workshops and origin from the churches and the museums of Gdańsk, Pelplin and Poznań. The general aim of this work was to analyze and systematize of how the technique and the technology of painting the blue layers had been changing from the mid-sixteenth to the end of the eighteenth century. The commonly used blue pigments were natural azurite, natural ultramarine and smalt, and since the beginning of the eighteenth century the only one blue pigment was organic indigo. The performed analysis is a database on ways of developing the blue painting layers in Gdańsk School of Painting and it will be helpful when comparing with other works both schools of Gdańsk, as well as the other European schools.